2009
DOI: 10.3181/0811-rm-346
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum Acetate Inhibits Vascular Calcification Induced by Vitamin D3 Plus Nicotine in Rats

Abstract: Lanthanum, a rare earth element, has been used to decrease serum phosphorus level in patients with chronic renal disease and hyperphosphatemia. We aimed to observe the effect and mechanism of two doses of lanthanum acetate (375 and 750 mg/kg/day) on vascular calcification induced by vitamin D3 plus nicotine treatment in rats for 4 weeks. As compared with control rats, rats with calcification showed widespread calcified nodules and irregular elastic fibers in calcified aorta on von Kossa calcium staining and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Experimental studies have reported beneficial effects of lanthanum on reduction of VC 18–20 . Whether this benefit is related to effective phosphate reduction with lanthanum or additional mechanisms is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies have reported beneficial effects of lanthanum on reduction of VC 18–20 . Whether this benefit is related to effective phosphate reduction with lanthanum or additional mechanisms is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have reported beneficial effects of lanthanum on reduction of VC. [18][19][20] Whether this benefit is related to effective phosphate reduction with lanthanum or additional mechanisms is unclear. One study involving lanthanum administered to rats demonstrated suppression of osteoblastic differentiation of vascular smooth muscle cells, an effect perhaps mediated by activation of several pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematoxylin–eosin (HE) and Von Kossa staining were respectively carried out in these sections (Zhou et al . , ). Von Kossa staining was used to observe calcium deposits in aorta.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies in animals suggest that the noncalcium-based phosphate binder lanthanum, as well as calcimimetic drugs, may decrease vascular calcification, but this has yet to be verified in humans or linked to reduced mortality (33,34). Human trials involving the use of a wide range of therapies including VDRAs (35), calcimimetics (36), bisphosphonates (37), and sodium thiosulfate (38) are planned or already underway.…”
Section: Potential Therapiesmentioning
confidence: 99%